Impact of Risk Management and Good Corporate Governance on Firm Value in Sharia Commercial Banks for The 2018-2022 Period - Lusiana Yulianti, Maria; Roswinna, Winna; Sukmayana, Dodi; Damayanti, Febriyani; Nuryasintia, Indri (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This research is to look at the influence of Risk Management and Good Corporate Governance on Company Value (Empirical Study of Sharia Commercial Banks 2018-2022). The type of data used in this research is qualitative and quantitative data. The population in this research is Sharia Commercial Bank companies registered with the Financial Services Authority on the Islamic banking statistics website in 2018-2022, totaling 14 companies with research samples using census techniques, namely the entire population was sampled using multiple linear regression. The results of this research show that both partial and simultaneous risk management have a significant positive effect on company value. The better the implementation of risk management in sharia commercial banks, which is reflected in non-performing loans above 5%, the higher the company value in the sharia bank will be. Good corporate governance (GCG) has a significant positive effect on company value. This means that the better the implementation of good corporate governance (GCG) in sharia commercial banks, the greater the company value of the sharia commercial bank will be.